NMR metabolite comparison of local pigmented rice in Yogyakarta - Dio N. Wijaya; Febri Adi Susanto; Yekti Asih Purwestri; Dyah Ismoyowati; Tri Rini Nuringtyas (Universitas Gadjah Mada, 2017)
Pigmented rice may have a black or red color due to higher anthocyanin content in its grain. A natural antioxidant, many studies on anthocyanin have reported its positive effects on human health. This fact has spurred the development of pigmented rice as a functional food. This study aimed to compare the metabolite profiles of black and red rice. Three black rice cultivars, namely Melik, Pari Ireng, and Cempo Ireng Sleman, and two red rice cultivars, Inpari 24 and RC 204, were used. After husk removal, grain samples were ground in liquid nitrogen and dried with a freeze dryer. The dried samples were extracted using 50% MeOD4 (in a D2O phosphate buffer pH 6 containing 0.01% TSP as an internal standard). Metabolomic analysis was performed using 500 MHz NMR followed by multivariate data analysis. An orthogonal partial least squares-discriminant analysis (OPLS-DA) model ađer PCA was constructed to discriminate between the five different cultivars. The resulting OPLS-DA score plot revealed a clear separation between black rice and red rice. The metabolites that could influence the separation of red rice and black rice were valine, threonine, alanine, glutamate, galactinol, β-glucose, α-glucose, raffinose, and fumaric acid.